The exocyst in ciliogenesis - Brennan Winkler; Kasey Lerner; Joshua H. Lipschutz (Renal Failure)
The primary cilium is an organelle found on different cell types in many organs, and is important for human health including the kidney. Diseases due to abnormal or absent cilia are termed ciliopathies and ADPKD is one of the most common ciliopathies and the fourth leading cause of ESKD. The mechanisms of how primary cilia work remain incompletely understood. One particular axis of ciliary function that is especially unclear is the role of the highly-conserved eight-subunit exocyst trafficking complex, which is critically involved in transporting proteins from the trans-Golgi network to the cilium. The goal of this review article is to cover key aspects of exocyst function, how these are known to or are predicted to impinge on ciliary function, and to point out areas that need further research. The exocyst has been shown to be regulated by many different small GTPases of the Rho, Ral, Rab, and Arf families which likely give the exocyst specificity of function. The exocyst has been implicated in several intracellular signaling pathways involving the cilium including the MAPK and phosphoinositide pathways. The exocyst and its regulators have also been found in urinary extracellular vesicles suggesting that the exocyst may be involved in ‘urocrine’ signaling and repair following AKI. There is an urgent need to develop new strategies to address exocyst function in the context of cilia, which will greatly benefit our understanding of cilia as well as how disrupted exocyst function in cilia leads to disease, which, in turn, should lead to novel therapeutics.